Mikania (asteraceae, eupatorieae) no estado da Bahia. - Cardoso, Andréia Gandara (2017)
Mikania (Asteraceae, Eupatorieae) in Bahia state − The Alliance Heliantheae (Asteraceae) has been established as a monophyletic group from molecular studies. The group is divided into 13 tribes which together contain 20−25% of the Asteraceae species. The Eupatorieae Tribe, one of the tribes belonging to the Alliance, presents ca. 2200 species, grouped into 182 genera and 19 subtribes. In Brazil, the tribe stands out for having the highest number of genera (86) and species (615) in the various phytophysiognomies of the country. Mikania, considered one of the most natural and complex of the Tribe Eupatorieae, belongs to the subtribe Mikaniinae and presents ca. 450 species with mainly neotropical distribution. In Brazil, the genus is represented by 203 species, of which 142 are considered endemic. The present work had as objective to carry out the floristic survey and the taxonomic study of the species of Mikania (Asteraceae, Eupatorieae) in Bahia state. Field collections were performed in several municipalities of the state, besides to the visit to important national herbaria for the group (ALCB, CEPEC, HUEFS, HRB, RB, R, SP and SPF). Of the 53 names previously registered for Bahia, 14 were excluded, 7 new occurrences were added, totalizing 46 species. We present a key identification, descriptions of all species, as well as taxonomic, biological and geographic distributioncomments